Effect of grain fermentation and malting time on nutrient and anti nutrient composition of biscuits from Aksum finger millet (Eleusine coracana) - Ayele Assefa Adugna; Getachew Neme Tolesa; Solomon Abera; Girma Daba Deme (Cogent Food & Agriculture)
Finger millet grain is healthy and high in protein, fat and minerals especially calcium after proper processing. However, antinutrients represent a major obstacle to the usage of finger millet grains, which have restricted dietary applications. Biscuits are typically made from wheat flour, which increases wheat demand despite restricted supplies. The study aimed to explore how the length of fermentation and grain malting affected the color, nutritional content and antinutrients value of Aksum finger millet biscuits. Fermentation times were 24, 36 and 48 hours while the malting times were 24, 48 and 72 hours. The raw grain flour biscuit was used as a control sample to compare with each six samples of both factors. The moisture content of biscuits ranged from (5.64–8.00%), crude protein (6.60–10.09%), crude fat (12.12–17.30%), crude fiber (3.20–3.95%), total ash (1.55–2.19%), carbohydrate (70.81–75.50%) and energy content (439.50–479.51 Kcal/100 g) showing significant (P < 0.05) differences due to fermentation and malting duration. The results of zinc, iron and calcium were 1.80–2.36, 2.30–3.31 and 358.00–377.09 mg/100 g, respectively. The tannin and phytic acid content were significantly reduced from 1.21 to 0.78 and 435.50 to 430.78 mg/100g. The control biscuit had a good color value, but the biscuit samples exhibited significant (P < 0.05) reductions in their L*, a* and b* values due to fermentation and malting time. The result showed that grain fermentation and malting periods increased the proximate composition and mineral contents while decreasing the antinutrient content of the biscuits. In general, the acceptance of biscuits were enhanced by fermentation and malting.